The circadian control of sleep. - Fisher, S; Foster, R; Peirson, S (2013)
The sleep/wake cycle is arguably the most familiar output of the circadian system, however, sleep is a complex biological process that arises from multiple brain regions and neurotransmitters, which is regulated by numerous physiological and environmental factors. These include a circadian drive for wakefulness as well as an increase in the requirement for sleep with prolonged waking (the sleep homeostat). In this chapter, we describe the regulation of sleep, with a particular emphasis on the contribution of the circadian system. Since their identification, the role of clock genes in the regulation of sleep has attracted considerable interest, and here, we provide an overview of the interplay between specific elements of the molecular clock with the sleep regulatory system. Finally, we summarise the role of the light environment, melatonin and social cues in the modulation of sleep, with a focus on the role of melanopsin ganglion cells.